Cabo Blanco: a Lower Jurassic outcrop in the northeastern Deseado Massif, Patagonia - Márquez, Marcelo J. (2023)
The Cabo Blanco outcrop, located in the northeastern Deseado Massif on the Atlantic coast of Patagonia, exposes metasedimentary rocks affected by contact metamorphism. The area presents three main lithofacies associations—breccias and conglomerates from debris flows, stratified sandstones deposited in shallow subaqueous settings, and mudstones from calmer environments—indicating sedimentation in a lake or marine system. U-Pb zircon dating from fine-grained sandstones yielded Early Jurassic ages (around 185 Ma), linking the outcrop to the initial magmatic stages of the Chon Aike silicic large igneous province. The zircons’ euhedral morphology suggests an igneous origin later reworked into a subaqueous depositional environment.